HERBAL MEDICINAL PRODUCTS IN A TREATMENT OF MASTALGIA IN GYNECOLOGIC PATIENTS - A. G. Kedrova; S. A. Levakov (Опухоли женской репродуктивной системы, 2017)
Implementation of breast cancer screening using digital mammography improved the diagnosis of primary proliferative regressive structural changes in the breast, manifested as diffuse or diffusely-nodal deformations of tissues. Currently, women are significantly more likely to seek medical consultation for damages of the breast that could not be evaluated earlier. This requires the development of special tactics for their treatment and follow-up. Nowadays, searching for prognostic markers and choosing adequate therapy for nodular and diffuse mastopathy are among the most discussed issues in mammology, because up to 25 % of all breast cancer cases are diagnosed during the in situ phase. In this article we try to reassess the problem of dyshormonal changes in the breast and develop an optimal approach to their treatment.